2009
DOI: 10.1186/bcr2234
|View full text |Cite
|
Sign up to set email alerts
|

T-cell metagene predicts a favorable prognosis in estrogen receptor-negative and HER2-positive breast cancers

Abstract: Introduction Lymphocyte infiltration (LI) is often seen in breast cancer but its importance remains controversial. A positive correlation of human epidermal growth factor receptor 2 (HER2) amplification and LI has been described, which was associated with a more favorable outcome. However, specific lymphocytes might also promote tumor progression by shifting the cytokine milieu in the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
371
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(402 citation statements)
references
References 55 publications
25
371
1
5
Order By: Relevance
“…18,29,30 Therefore, although a number of gene expression signatures have been published revealing high levels of molecular heterogeneity in immune infiltration, [31][32][33][34] pathological assessment remains critical for discerning tumor spatial heterogeneity. Lymphocytes can be identified based on their typical morphology of small, round and homogeneously basophilic nuclei which differentiates them from other leukocytes, such as neutrophils with more elongated and segmented nuclei.…”
Section: Immune Cellsmentioning
confidence: 99%
“…18,29,30 Therefore, although a number of gene expression signatures have been published revealing high levels of molecular heterogeneity in immune infiltration, [31][32][33][34] pathological assessment remains critical for discerning tumor spatial heterogeneity. Lymphocytes can be identified based on their typical morphology of small, round and homogeneously basophilic nuclei which differentiates them from other leukocytes, such as neutrophils with more elongated and segmented nuclei.…”
Section: Immune Cellsmentioning
confidence: 99%
“…It is an antibody-drug conjugate cancer-killing agent combined with targeted antibody trastuzumab (Herceptin). A study has demonstrated that in 25% of breast cancer females who were victims' of HER2 overexpression, T-DM1 frequently overcomed the breast tumors and allowed the patients to go into remission (Rody et al, 2009;Yu-Ting et al, 2011).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…These studies describe clusters of coordinately expressed genes that quantify the relative abundance and functions of tumor infiltrating immune cell populations and associate with patient outcomes. 1418 In a recent report, we described three such prognostic immune signatures in breast tumors, each comprised of tens of genes with immune-specialized functions and expression patterns unique to immune cell populations. 1921 These signatures, or metagenes, reflect the intratumoral presence of different immune cell lineages: T cells/NK cells (T/NK metagene) comprised of genes with functional roles in cytotoxic T-cell and NK-cell activation, B cells/plasma cells (B/P metagene) marked by IgG antibody isotype-related genes, and Myeloid/Dendritic cells (M/D metagene) delineated by genes encoding myeloid-specific and MHC-class II antigen-presenting molecules.…”
Section: Introductionmentioning
confidence: 99%